Computed tomography and magnetic resonance imaging of pulmonary hypertension: pulmonary vessels and right ventricle - Ley, Sebastian; Grünig, Ekkehard; Kiely, David G.; van Beek, Edwin; Wild, Jim (Journal of magnetic resonance imaging, 2010)
Pulmonary hypertension (PH) is very heterogeneous and the classification identifies five major groups including many associated disease processes. The treatment of PH depends on the underlying cause and accurate classification is paramount. A comprehensive assessment to identify the cause and severity of PH is therefore needed. Furthermore, follow-up assessments are required to monitor changes in disease status and response to therapy. Traditionally, the diagnostic imaging work-up of PH comprised mainly echocardiography, invasive right heart catheterization, and ventilation/perfusion scintigraphy. Due to technical advances, multidetector row computed tomography (CT) and magnetic resonance imaging (MRI) have become important and complementary investigations in the evaluation of patients with suspected PH. Both modalities are reviewed and recommendations for clinical use are given.
Gesehen am 14.03.2023